Missionaries of the Sacred Heart of Mary and the Catholic Hospital of Guisui - LIU Qingyu, (Journal of Research for Christianity in China (JRCC), 2025)
Since modern times, missionaries from the Congregation of the Sacred Heart of Mary have carried out missionary work in Inner Mongolia for over 80 years, actively establishing medical, charitable, and educational institutions during this period. This article introduces the Guisui Catholic Hospital founded by Sacred Heart missionaries and outlines its medical activities. It analyzes and summarizes the hospital's profound impact on Inner Mongolia's modern social history, affirming its contributions to the region's contemporary medical development.